The effects of gesturing, blocked order, and incremental presentation in foreign language learning - Chin, Simone L (ProQuest Dissertations & Theses, 2014)
Research in second language acquisition reveals that adults have difficulty learning the grammatical aspects of a foreign language. The present study investigated the efficacy of three teaching methods that were predicted to help adults better learn the grammar of a foreign language. First, lessons were presented in small pieces that gradually increased to full sentences. Second, lesson trials were blocked such that multiple examples of sentences with the same object or verb were presented consecutively. Third, participants were instructed to gesture the actions of the verbs within sentences. All three methods were predicted to increase the likelihood of learning the grammar form of sentences through guiding adults’ attention to fewer components of language input at a time. In Experiment 1, 82 English native speakers played an adventure videogame designed for the learning of French vocabulary and grammar of French sentences for two one-hour sessions. All three methods were incorporated in the lessons portion of the game resulting in a 2(incremental vs. full sentence) X 2(blocked vs. unblocked order) X 2(gesture vs. no gesture) between subjects design. The results from Experiment 1 revealed a) more nouns were acquired than verbs and b) a trend that the incremental conditions performed worse than the full sentence conditions on the grammar measures. In Experiment 2, 110 adult learners played the French videogame, but only the blocked presentation and gesture imitation methods were incorporated in the lessons portion (omitting the method of incremental presentation). The results from Experiment 2 revealed a) conditions with either method of blocked presentation or gesturing performed better on vocabulary and grammar measures than the unblocked non-gesture condition, and b) the combination of blocked presentation and gesturing led to better learning of inductive grammar than either method alone. The outcome of the study suggests gesturing and blocked order teaching methods that encourage adults to attend to a few but important components within a sentence are advantageous in learning the grammar of a foreign language.